An Open and Multi-Layer Web Platform for Higher Music Education - Adriano Baratè; Luca Andrea Ludovico (Je-LKS: Journal of E-Learning and Knowledge Society, 2020)
This paper describes an open platform for the advanced experience of music information. Based on the IEEE 1599 standard, such an environment supports an integrated and synchronized multi-layer description of music pieces. This approach can be particularly suitable in higher music education, where the structured organization of a multiplicity of free resources can foster advanced and engaging learning activities. After addressing the subject of openness in music education and introducing the key features of the IEEE 1599 format, some clarifying examples and educational scenarios will be discussed.